تحديد التوزيع الجغرافي لدرجة الأسفلت داخل ليبيا وفق نظام تصنيف الأسفلت عالي الأداء (Journal of Academic Research, 2025)
Asphalt binder is one of the essential components of hot mix asphalt (HMA). The proper selection of asphalt binder grade depends on many factors, including traffic volume, air temperatures, and other conditions that vary depending on the study area. Asphalt grading systems have been updated and new systems were developed in order to address pavement distresses and achieve highly durable pavement.This study aims to implement SUPERPAVE grading system in Libya, which consists of asphalt binder grade selection, mix design, and performance evaluation. This facilitates the process of selecting the appropriate asphalt grade for each geographical area. Asphalt binder specifications in Libya are based on the penetration grading system, which lacks a comprehensive assessment of binder behavior and long-term pavement performance.This study utilizes data collected from 23 meteorological stations in Libya over 20 years. Pavement temperature was calculated using four models to predict asphalt binder grade. The results at 98% reliability showed that SHRP and LTPP models classified Libya into three regions. PG 76-10 was assigned to Ghadames and Kufra regions, PG 64-10 to the eastern coast, and PG 70-10 to the remaining regions. SHRP and LTPP predictions were adjusted for slow speeds and high traffic volumes, and the results showed an increase of 4 grades in most stations. The high PG grade was also increased approximately one grade according to the ICM model, and by an average of two grades according to the Damage-Based model.